From Pathological Dependence to Healthy Independence - Liz Jamieson; Pamela J. Taylor; Barry Gibson (Grounded Theory Review: An International Journal)
People with mental disorder are admitted to high security hospitals because of perceived risk of serious harm to others. Outcome studies generally focus on adverse events, especially reoffending, reflecting public and government anxieties. There is no theoretical model to provide a better basis for measurement. There have been no studies examining discharge from the perspectives of those involved in the process. This paper begins to fill this gap by generating a grounded theory of the main concerns of those involved in decisions to discharge from such hospitals. Data were collected by semi-structured interviews with staff of various clinical and non clinical disciplines, some with a primary duty of care to the patient, while mindful of public safety, and some with a primary duty to the public, while mindful of patients’ rights. The data were analysed using a grounded theory approach. Their main concern was ‘pathological dependence’ and that was resolved through the process of ‘facilitating independent living’. Clinicians and non-clinicians alike managed this by ‘paving the way’ and ‘testing out’. The former begins on hospital admission, intensifies during residency, and lessens after discharge. Testing out overlaps, but happens to a greater extent outside high security. Factors within the patient and/or within the external environment could be enhancers or barriers to movement along a dependence-independence continuum. A barrier appearing after some progress along the continuum and ending independence gained was called a ‘terminator’. Bad outcomes were continuing or resumed dependency, with ‘terminators’, such as death, re-offending or readmission, modelled as explanations rather than outcomes per se. Good outcomes were attainment and maintenance of community living with unconstrained choice of professional and/or social supports. Although this work was done in relation to high security hospital patients, it is likely that the findings will be relevant to decision making about departure from other closed clinical settings.